The rise and progress of classical archaeology : with special reference to the University of Cambridge, an inaugural lecture (Cambridge university press, 1931)
Originally published in 1931, this book presents the content of an inaugural lecture delivered at Cambridge University by Arthur Bernard Cook (1868-1952) upon taking up the position of Laurence Professor of Classical Archaeology. The text provides a discussion of the development of classical archaeology with special reference to Cambridge University.